2016
DOI: 10.1155/2016/1015390
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Receptor for Advanced Glycation End Product Ameliorates Chronic Intermittent Hypoxia Induced Renal Injury, Inflammation, and Apoptosis via P38/JNK Signaling Pathways

Abstract: Obstructive sleep apnea (OSA) associated chronic kidney disease is mainly caused by chronic intermittent hypoxia (CIH) triggered tissue damage. Receptor for advanced glycation end product (RAGE) and its ligand high mobility group box 1 (HMGB1) are expressed on renal cells and mediate inflammatory responses in OSA-related diseases. To determine their roles in CIH-induced renal injury, soluble RAGE (sRAGE), the RAGE neutralizing antibody, was intravenously administered in a CIH model. We also evaluated the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 62 publications
2
34
0
Order By: Relevance
“…Moreover, the apoptotic ratio of cerebrovascular cells was calculated in red fluorescence stained with CD31 and brown in TUNEL assay. CD31 was a marker of vascular cells43. Thus, vascular cells were marked in red fluorescence and counted.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the apoptotic ratio of cerebrovascular cells was calculated in red fluorescence stained with CD31 and brown in TUNEL assay. CD31 was a marker of vascular cells43. Thus, vascular cells were marked in red fluorescence and counted.…”
Section: Resultsmentioning
confidence: 99%
“… 50 It is also reported that chronic inflammatory and apoptotic cascades that are stimulated by p38 and JNK, but not ERK pathways, contribute to the pathogenesis of the chronic intermittent hypoxia-induced renal injury. 51 These studies suggest that MAPKs are differentially involved in cellular responses to hypoxic stress, depending on cell type and cell conditions. However, the precise functions of ERK1/2 and p38 are still debatable, especially in the kidney under hypoxic conditions.…”
Section: Discussionmentioning
confidence: 98%
“…et al, 2017) and protective role of ERK1/2 (Hung et al, 2003;Chen et al, 2015;Li et al, 2018) in cell survival under stress, the up-regulation of P-ERK1/2 in hypoxic renal cells is probably an adaptive response to overcome the hypoxia-induced increase in P-p38, rendering the cells a new balance between ERK1/2 and p38. Indeed, there is solid evidence indicating that P-ERK1/2 is a mediator of controlling cell survival in response to many stimuli including hypoxia in the kidney (di Mari et al, 1999;Kunduzova et al, 2002;Yang et al, 2003;Zou et al, 2016), while the p38 is considered as the major stress-activated protein kinases (Kyriakis and Avruch, 2012) and mediate a pro-inflammation effect in hypoxic condition (Wu et al, 2016). Based on our previous work, we believe that DOR, which was tolerant to hypoxia and was not down-regulated in the renal cells after hypoxia, plays a positive effect in the upstream signaling of P-ERK1/2 and a negative influence on p38, at least partially.…”
Section: Discussionmentioning
confidence: 99%